The consequence of the closure of primary care dental services on secondary care during the COVID-19 pandemic - A national outlook - Constance Hardwick; Ellie Day; Edward Carlton; Tom Dudding (Elsevier, 2024)
Background: After the global pandemic of COVID-19 in March 2020, restrictions were implemented on all aspects of routine dental-care with a primary focus to urgent care only. Aim: To investigate the impact on secondary care medical facilities and Emergency Department (ED) admissions for the management of severe dental infections as a result of restricted access to routine primary dental-care during the period of COVID-19 restrictions. Design: National level Hospital Episode Statistics was used to describe the number of inpatient admissions for the drainage of a dental abscess and the attendance for dental related to ED. Data was stratified across ethnicity, sex and deprivation. Results: There was a decrease in admission to secondary care for dental infection and total admissions during the initial period of national lockdown due to COVID-19. Incidence of dental abscess drainage equalled 4.51 per100,000 person years from 2018 to 2021. There was a 209 % increase in admissions in patients with greatest deprivation. This was much more exaggerated compared to that of non-dental comparison conditions and total inpatient admissions. Using subsequent inpatient admission as a marker of severity, 4.2 % dentally related ED attendance required onward admission. Conclusion: A large proportion of ED attendances with dental related conditions did not require inpatient admission, therefore a large proportion of ED attendances could be managed more appropriately in specific dental services. Dental infections requiring surgical admission disproportionality affects the most deprived communities of the population which is much more exaggerated compared to peri-anal and total inpatient admissions. This highlights the inequalities and links with deprivation that exist in oral and dental health in England, which is much greater than that of general health if total admissions are used as maker for this. This research highlights the need to improve access to primary dental-care services.